The definition of apartheid in customary international law and the international convention on the elimination of all forms of racial discrimination - Jackson, M (Cambridge University Press, 2022)
Despite recent and increasing attention to the wrong of apartheid in international politics, some basic definitional questions remain uncertain. This article seeks to delineate the definition of apartheid in international law. Its focus is on the prohibition of apartheid binding States in custom and the obligation in Article 3 of the International Convention on the Elimination of All Forms of Racial Discrimination. In both cases, the article shows that the Apartheid Convention of 1973 supplies the wrong's definition. Thereafter, the article addresses three key elements that will be central to determining an allegation of apartheid: its wrongful acts, its distinctive purpose requirement, and the issue of what constitutes a ‘racial group’. Finally, the article also draws attention to the wider importance of the prohibition of apartheid in the international legal system. International law marks with particular normative significance a set of practices entailing systematic and structural harms that need not involve violations of life or bodily integrity.